Development of STEM ethnoscience electronic module on environmental preservation material to improve students' science process skills - Siti Alisah; S. Sajidan; M. Muzzazinah (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The urgent need for teachers and students for innovative learning media that integrates local context (ethnoscience), and technology (STEM) to improve students' science process skills is the main basis for the development of this electronic module. This study aims to produce an interactive STEM ethnoscience science electronic module. The development of this electronic module is based on the ADDIE from Branch, R. M. The feasibility test of the STEM ethnoscience science electronic module uses validity and readability tests. The validity test of the electronic module was carried out by experts in the field of Science Education and the readability test by student respondents using a questionnaire. The results of the needs analysis were used to design the STEM ethnoscience science electronic module. This electronic module is compiled STEM syntax with 4 stages of learning, namely let's imagine, let's practice, let's read and let's evaluate. The results of the study showed that this STEM ethnoscience science electronic module was feasible, with an average content validity value of 0.94 and a percentage of readability of the electronic module of 91%. Electronic module is recommended as an innovative digital teaching material option to support science education integrated with culture and technology, while enriching STEM education practices.